Planning Method of a Comprehensive District Plan: Studies on making a comprehensive district plan in rural areas by inhabitants (IV) - USHINO, Tadashi (Transactions of The Japanese Society of Irrigation, Drainage and Reclamation Engineering, 1995)
To implement farm land consolidation that takes into consideration mobilization of land for agricultural use and formation of land use order (planning subjects), a conflict model of a rural planning system is effective. One of the effective factors is that the “Kande method” is effective as a planning method for a comprehensive district plan. This paper compares the results of the applied examples of the “Kande method” as a planning method of a conflict model, with which is a “combined farming and residential area method” and makes clear the mechanism of the effectiveness of the “Kande method”. (1) The reasons why the “Kande method” is effective are because the planning process of the “Kande method” is performed in the following three steps; 1) the inhabitants recognize the problems and possibilities (or potentialities) of a district (the step of making up and examining a written investigation of self survey), 2) basic principles of a plan are established (the step of making up and examining a written plan for a pilot plan), 3) a planning authority builds consensus on a comprehensive district plan (the step of making up and examining a written plan for a master plan).(2) Each member of a planning organization, which is composed of settlement leaders, settlement residents, self-government body and planners, communicate with one another, learn systematically the planning subjects of the district, reform their way of thinking and perform planning subjects of the district.(3) On the other hand, the “mixed farming and residential area method” dosen't have such mechanisms.